Clinical characteristics of 54 medical staff with COVID‐19: A retrospective study in a single center in Wuhan, China. Issue 7 (6th April 2020) - Chu, Jiaojiao; Yang, Nan; Wei, Yanqiu; Yue, Huihui; Zhang, Fengqin; Zhao, Jianping; He, Li; Sheng, Gaohong; Chen, Peng; Li, Gang; Wu, Sisi; Zhang, Bo; et al.
Abstract: In December 2019, an outbreak of the severe acute respiratory syndrome coronavirus 2 (SARS‐Cov‐2) infection occurred in Wuhan, and rapidly spread to worldwide, which has attracted many people's concerns about the patients. However, studies on the infection status of medical personnel is still lacking. A total of 54 cases of SARS‐Cov‐2 infected medical staff from Tongji Hospital between 7 January and 11 February 2020 were analyzed in this retrospective study. Clinical and epidemiological characteristics were compared between different groups by statistical method. From 7 January to 11 February 2020, 54 medical staff of Tongji Hospital were hospitalized due to coronavirus disease 2019 (COVID‐19). Most of them were from other clinical departments (72.2%) rather than emergency department (3.7%) or medical technology departments (18.5%). Among the 54 patients with COVID‐19, the distribution of age had a significant difference between non‐severe type and severe/critical cases (median age: 47 years vs 38 years; P  = .0015). However, there was no statistical difference in terms of gender distribution and the first symptoms between theses two groups. Furthermore, we observed that the lesion regions in SARS‐Cov‐2 infected lungs with severe‐/critical‐type of medical staff were more likely to exhibit lesions in the right upper lobe (31.7% vs 0%; P  = .028) and right lung (61% vs 18.2%;  P  = .012). Based on our findings with medical staff infection data, we suggest training for all hospital staff to prevent infection and preparation of sufficient protection and disinfection materials.